Financial Technology in Indian Finance Market - K. Srinivasan; Dr. S. Rajarajeswari (International Journal of Engineering and Management Research, 2021)
The purpose of this paper is to discuss issues such as fintech drivers, shortcomings of traditional financial services, and the role of technological advancement. The paper also addresses issues concerning fintech investment and disruption. It refers to financial technology challenges such as investment management, customer management, and regulation. The paper examines the evolution of fintech in the global market over time.